The Inclusion of Children with Special Needs in Folklore Activities in Slovenian Schools with a Special Educational Programme - Kovačič, Bojan; Černela, Nejc; Licardo, Marta (Selected Contemporary Research on Special Needs, Giftedness, and Talent in Slovenia, 2025)
Using a representative sample (240 professionals from all 28 Slovenian primary schools with a special educational programme), we partially confirmed the hypothesis, which states that professionals who teach in schools with a special education programme agree with the statements about the inclusion of students with special needs in folklore activities. The hypothesis, which asserts that there are statistically significant differences between groups of professionals (special and rehabilitation pedagogues, special needs teachers, inclusive pedagogues, social pedagogues, teachers with special pedagogical qualifications and other pedagogical staff) regarding their agreement with statements referring to the inclusion of students with special needs in folklore activities in schools with a special education programme, was rejected based on the results obtained.